Advancing Environmental Protection through Legislative Measures: Case Studies and Best Practices (Lex localis - Journal of Local Self-Government, 2025)
The article evaluates the role of laws and legislative initiatives in protecting the environment and promoting a best practice with relevant case studies. The environment is critical to supporting life on Earth, and it must be protected for present and future generations.  Governments around the world have recognized the importance of comprehensive legal and policy frameworks for effectively addressing environmental concerns. This article looks at numerous worldwide, national, and regional laws and legislative initiatives aimed at safeguarding the environment, conserving natural resources, and mitigating the harmful effects of human activity. The report also emphasizes the importance of multidisciplinary approaches, stakeholder participation, and enforcement mechanisms in ensuring the success of environmental laws. By analyzing case studies and examples, the essay demonstrates the positive influence of strong legislation.